Antibody responses against heterologous H5N1 strains for an MF59-adjuvanted cell culture-derived H5N1 (aH5n1c) influenza vaccine in adults and older adults - Sharon S. Frey; Eve Versage; Esther Van Twuijver; Matthew Hohenboken (Taylor & Francis Group, 2023)
MF59-adjuvanted H5N1, cell culture-derived inactivated influenza vaccine (aH5N1c, AUDENZ®, Seqirus) is available for persons 6 months of age and older. During a pandemic, lack of preexisting immunity to novel influenza strains increases morbidity and mortality. This study examined the potential for an adjuvanted vaccine to provide cross-protection to novel viruses. Two similarly designed studies involving separate cohorts aged 18-64 and ≥65 y assessed immune responses to five heterologous H5N1 influenza strains elicited by two 7.5 μg doses of aH5N1c given 3 weeks apart. Geometric mean titers (GMT) on Days 1 and 43 and Day 43/Day 1 geometric mean ratios (GMRs) were determined with hemagglutination inhibition (HI) and microneutralization (MN). Rates of seroconversion (SC) and percentages of subjects with HI and MN ≥ 1:40 were determined. Significant increases in GMTs were observed on Day 43 after vaccination for all 5 heterologous strains in all ages tested. SC rates were 28-55% and 17-46% among those aged 18-64 and ≥65 y, respectively. MN ≥ 1:40 was observed in 38-100% of younger and 37-97% of older subjects, and HI ≥ 1:40 was achieved by 28-64% of subjects aged 18-64 y and by 17-57% of subjects aged ≥65 y. A SC rate ≥40% (97.5% CI) was met for two heterologous strains tested in adults aged 18-64 y. In adults aged 18-64 and ≥65 y, two 7.5 μg doses of aH5N1c demonstrated increased immunogenicity from baseline against five heterologous H5N1 strains, illustrating the potential for aH5N1c to provide cross-protection against other H5N1 strains.